Price Cutting and Business Stealing in Imperfect Cartels - Bernheim, B. Douglas; Madsen, Erik (American Economic Review, 2017)
Although economists have made substantial progress toward formulating theories of collusion in industrial cartels that account for a variety of fact patterns, important puzzles remain. Standard models of repeated interaction formalize the observation that cartels keep participants in line through the threat of punishment, but they fail to explain two important factual observations: first, apparently deliberate cheating actually occurs; second, it frequently goes unpunished even when it is detected. We propose a theory of equilibrium price cutting and business stealing in cartels to bridge this gap between theory and observation. (JEL D43, L12, L13)